Interactive Methods in Teaching Noun Class Categories in Primary Grades - M. H. Ergashova (Scholars Digest Publishing, 2023)
In this article, methods and ideas on forming the concept of “number” in the noun phrase, teaching noun phrase categories in primary grades are expressed. This article is relevant as it provides theoretical information about the selected methods and interactive methods within the framework of the four stages of primary classes, as well as revealing practical application guidelines.
Keywords: number, singular, plural, method of comparison, lexical unit, scheme, program, independent vocabulary, interactive method, lexical group, method, category,functional forms, possession, agreement, “T ” scheme.